Weight Management, Energy Metabolism, and Endocrine Hor¬mones- Review Article - Seyed-Ali MOSTAFAVI; Saeed HOSSEINI (Tehran University of Medical Sciences, 2015)
Energy expenditure is determined by basal metabolic rate, physical activity, and Thermic Effect of Foods (TEF). Some endocrine hormones have role in basal metabolism and hence in human energy expenditure. And some foods pose more thermic effects on the total body energy expenditure and therefore can influence body weight. This review was performed to discuss factors which may affect body metabolism and body weight. Latest medical databases and nutrition and metabolism books were reviewed. We used the following keywords in online databases: "Weight Management" and "Hormones"; "Energy Metabolism" and "dietary factors"; "Weight Management" and "dietary factors"; "Endocrine Hormones" and "energy expenditure"; "Basal Energy Expenditure" and "dietary factors"; " Thermic Effect of Foods" and "dietary factors". The best designed articles were used to perform this review. The results are presented bellow. Spicy foods, Caffeine, and alcohol are some dietary factors and Body Size, Body Composition, Age and Gender are the non-dietary factors which may affect the metabolism. Diet composition can also slightly influence the metabolism. This effect depends on how efficient a dietary component is metabolized in the body. Regular dietary pattern also can slightly increase TEF comparing with irregular dietary pattern. Thyroid hormones, Ghrelin, Epinephrine, Cortisol, Steroid hormones, Leptin, Growth hormone, and insulin are among the most important hormones which may influence on metabolism and body weight. Energy expenditure is the basis for measuring human energy requirement and is crucial for weight management. Various hormonal, dietary and non-dietary factors are engaged in total body energy expenditure and are important for weight management.   Keywords: Weight Management, Energy Metabolism, Dietary factors, Endocrine Hormones